Development of radioiodine-labeled mequitazine for evaluation of hepatic CYP2D activity - Mizutani, Asuka; Kobayashi, Masato; Nishi, Kodai; Fujita, Ken-ichi; Takahashi, Kotaro; Muranaka, Yuka; Sato, Kakeru; Kitamura, Masanori; Suzuki, Chie; Nishii, Ryuichi; Shikano, Naoto; Magata, Yasuhiro; et al. (Frontiers in Pharmacology, 2024)
Background: As drug-metabolizing enzyme activities are affected by a variety of factors, such as drug-drug interactions, a method to evaluate drug-metabolizing enzyme activities in real time is needed. In this study, we developed a novel SPECT imaging probe for evaluation of hepatic CYP2D activity. Methods: Iodine-123- and 125-labeled 4-iodobenzylmequitazine (123/125I-BMQ) was synthesized with high labeling and purity. CYP isozymes involved in the metabolism of 125I-BMQ in mouse liver microsomes were evaluated, and the utility of 123/125I-was assessed from biological distribution and SPECT imaging evaluation in normal and CYP2D-inhibited mice. Results:In vitro metabolite analysis using mouse liver microsomes showed that 125I-BMQ is specifically metabolized by CYP2D. Biological distribution and SPECT imaging of 123/125I-BMQ in normal mice showed that injection 123/125I-BMQ accumulated early in the liver and was excreted into the gallbladder and intestines. In CYP2D-inhibited mice, accumulation in the liver was increased, but accumulation in the gallbladder and intestines, the excretory organ, was delayed. Since only metabolites of 125I-BMQ are detected in bile, visualization and measuring of the accumulation of metabolites over time in the intestine, where bile is excreted, could predict the amount of metabolites produced in the body and evaluate CYP2D activity, which would be useful in determining the dosage of various drugs metabolized by CYP2D. Conclusion:123/125I-BMQ is useful as a SPECT imaging probe for comprehensive and direct assessment of hepatic CYP2D activity in a minimally invasive and simple approach.